Characterization of critical stretch rate using outwardly propagating spherical flames - De la Rosa Urbalejo, Daniel; Martínez Martínez, Simón; Sánchez Cruz, Fausto (2018)
Outwardly propagating spherical flames within a constant volume combustion chamber (CVCC) are studied to analyse the non-linear relationship between flame stretch and flame speed, enabling a critical appraisal of a methodology proposed for characterizing the critical stretch rate. Four fuels, namely methane, propane, methanol and ethanol in air, are chosen to investigate the correlation between maximum critical stretch rate and the flame extinction across a range of equivalence ratios at various ambient conditions in under-driven flames, and to compare the hypothesis against data from the traditional counter-flowing flame technique. Flame propagation is recorded via high-speed Schlieren photography, and low ignition energies are achieved via a variable capacitive-discharge supply, enabling the critical early stages of flame propagation, critical stretch rate and the sensitivity of the non-linear methodology to ignition energy to be systematically analysed. The non-linear methodology shows partial agreement with extinction stretch rate from counter flowing flames, particularly in the case of gaseous fuels. Although the fuel vapour data lies between previous extinction stretch rate measurements using the counterflowing flame methodology, and predictions from chemical kinetic schemes, a 40% deviation is observed. A mathematical expression was produced to determine the critical stretch at the specific conditions of the present work.